2007
DOI: 10.1080/15287390600882663
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Induces Apoptosis in the Human Osteoblast-like Cell Line Saos-2

Abstract: Human exposure to the heavy metal cadmium has been associated with the development of bone diseases, including osteoporosis and osteomalacia. The mechanisms by which cadmium exerts a direct effect on bone remain unclear. Bone cells go through apoptosis for proper bone remodeling; therefore, it was hypothesized that cadmium disrupts this normal balance by inducing apoptosis. Human osteoblast-like cells (Saos-2) were treated with 10-200 muM cadmium chloride (CdCl2) and evaluated by trypan blue staining and phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 46 publications
1
36
1
Order By: Relevance
“…has been previously shown to interact with lipids similarly to Ca 2? (Girault et al 1998) and both ions contributed to the externalization of PS in other cell types, inducing apoptosis (Watjen et al 2002;Coonse et al 2007;Lee et al 2007;Sarang et al 2007). In contrast to our Hg 2?…”
Section: Assessment Of Metal Binding Affinity To Liposomescontrasting
confidence: 76%
“…has been previously shown to interact with lipids similarly to Ca 2? (Girault et al 1998) and both ions contributed to the externalization of PS in other cell types, inducing apoptosis (Watjen et al 2002;Coonse et al 2007;Lee et al 2007;Sarang et al 2007). In contrast to our Hg 2?…”
Section: Assessment Of Metal Binding Affinity To Liposomescontrasting
confidence: 76%
“…We mainly investigated the relationships between cadmium-associated biomarkers and bone metabolic markers, as well as ultrasonic bone evaluation parameters, because previous studies reported that bone absorption was accelerated by cadmium intake. The other parameters will be investigated in a further study [31][32][33][34][35][36][37][38][39][40][41][42]. Correlation between two substances in urine was calculated from the original measured values, adjusted by age and logarithmic transformed creatinine, while correlations between substances in urine and other parameters were calculated from values in urine corrected by urinary creatinine adjusted by age [43].…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in bone mineral density and inhibition of bone formation before the manifestation of renal dysfunction was reported in experimental animals [36]. Furthermore, Coonse and colleagues [37] reported that cadmium induced apoptosis in the cultured osteoblast-like cell line Saos-2. Thus, the possibility of a direct effect of cadmium on bone has been suggested [38].…”
Section: Discussionmentioning
confidence: 96%
“…Cadmium also interacts with renal mitochondrial hydroxylases of the vitamin D 3 endocrine complex, thereby contributing to skeletal injury. 5,6 Coonse et al 7 reported that cadmium induces apoptosis in the cultured osteoblast-like cell line Saos-2. Thus, there is a possibility of a direct effect of cadmium on bone health.…”
Section: Discussionmentioning
confidence: 99%